A forensic multiplex of nine novel pentameric-repeat STRs. (July 2017) - de la Puente, M.; Phillips, C.; Fondevila, M.; Gelabert-Besada, M.; Carracedo, Á.; Lareu, M.V.
Highlights: A novel 11-plex assay comprising 9 pentameric STRs and 2 Y-specific loci is presented. Pentameric STRs gave more than three-fold lower stutter ratios than tetrameric repeat loci of equivalent size. Reduction of stutter ratios can help interpretation of mixture DNA profiles in both CE- and MPS-based STR genotyping. Abstract: Pentameric-repeat short tandem repeats (STRs), consisting of loci with repeat units of five base-pairs, have the advantage of reduced stutter products compared to their tetrameric-repeat STR counterparts. This characteristic potentially helps the interpretation of mixed DNA profiles when minor component alleles may coincide with stutter peaks from the major components. To develop a simple but informative forensic multiplex with the capability to aid mixture interpretation, we designed an 11-plex assay of nine pentameric STRs new to forensic analysis plus two male- specific markers: DYS391 and the Y-Indel rs2032678 used in GlobalFiler™ (Life Technologies). East Asian-specific variation in the recently adopted Y-Indel rs2032678 is reported in this study for the first time in its forensic use as a sex marker. We estimated the levels of variation observed in the nine pentameric STRs in three of the major population groups sampled in the HGDP-CEPH human genome diversity panel: African, European and East Asian (combining individual populations as their sample sizes were too small for STR allele frequency estimations); and we include genotype data from a population sample of Northwest Spain. From this data, forensic informativeness metrics were estimated when applying the nine novel STRs in identification or kinship analyses. The assay was assessed for forensic sensitivity and ability to successfully genotype highly degraded DNA. In the profiles from the 11-plex assay we observed an average 2.15% stutter ratio in all the pentameric loci compared to 7.32% across equivalently-sized tetrameric STRs in the Promega Powerplex ® ESX-17 kit.